Adoption of Cloud-Based Accounting in the Villa Accommodation Sector: An Analysis of UTAUT Model Implementation - I Gusti Komang Aninda Trisna Wulandari; I Gusti Ayu Agung Pradnya Dewi (International Journal of Economics and Management Research, 2026)
This research aims to examine several factors that affect the adoption of cloud-based accounting in the villa accommodation sector in Badung Regency through the application of the UTAUT theoretical framework. The study was conducted using a quantitative approach through surveys of 100 respondents, including villa owners, managers, and financial staff who have used cloud-based accounting for more than one year. The data were analyzed using multiple linear regression with the assistance of SPSS software. The analysis results revealed a positive and significant relationship between Performance Expectancy, Effort Expectancy, and Social Influence with Behavioral Intention to adopt cloud-based accounting. The research model can explain 68.7% of the variation in Behavioral Intention, while the remaining variation is accounted for by other determinants outside the examined model. The findings indicate that perceptions of performance benefits, ease of use, and social context support play a significant role in strengthening the acceptance of cloud-based accounting in the villa sector. This study is expected to contribute to the enrichment of academic literature on accounting information systems and serve as a practical reference for villa business practitioners to optimize technology-based financial management